CE-23 Epidemiological aspects and drugs used in a cohort of chilean systemic lupus erythematosus patients. (31st August 2016) - Neira, Óscar; Muñoz, Luis; Maya, Juan; Miño, Cristóbal
Abstract : Background: Systemic lupus erythematosus (SLE) is a chronic autoimmune disease with unknown aetiology and a broad clinical expression. One important problem in the management of SLE is the access, and the adherence to drugs, especially in developing countries. Materials and methods: The national public health system (SNSS) covered the health for 73.2% of the Chilean population. Some diseases have been included in a special program of Health Specific Guarantees (GES), in order to assure full access to drugs. SLE was included in this program in 2013 and brings us the opportunity, by first time, to know the number of our patients. The pharmacy of our hospital has detailed registry of the outpatient prescribed and dispatched medication on SLE patients. The objectives are to describe the national prevalence and annual incidence of SLE patient in SNSS system. To describe the SLE drugs prescription profile in our hospital. Results: At the end of 2015 a total of 6.714 SLE patient had been registered in the SNSS GES system, 6.257 (93.2%) of them are women's. For this population the SLE prevalence is 50.7/100, 000, and the annual incidence is 9.2/100, 000. In our hospital at the end of 2015 there were 463 SLE GES patients. During 2015, 33.7% of them refilled medication at 12 month, and 32.4% got only 6 or less refills. The frequency of use and average dose of the different SLE medications on this group of patients is listed on Table 1 . Conclusions: We communicate prevalence and incidence rates for Chilean SLE patients similar to those reported elsewhere. A 66.3% of patients refill less medication that prescribed. The 82% are on low dose of prednisolone, 86% are on antimalarial and a 62% are on immunosuppressive drugs.